KERAGAMAN DAN KEMIRIPAN TUMBUHAN BAWAH DI AREA REKLAMASI PT ADARO INDONESIA - Sederi Sederi; Ahmad Jauhari; Badaruddin Badaruddin (Jurnal Sylva Scienteae, 2022)
Natural succession is an important process in the development of vegetation, especially on land that has been damaged, such as former coal mines. After mining coal as a raw material for making fuel, the ex-mining land has the characteristics of a site without top soil, high density, poor in nutrients, high pH and low soil microbial population. The condition of the ex-coal mining site that does not support colonization of natural plants has led to the introduction Cover crops, especially legume cover crops, are needed to improve site quality. Legume crops play a significant role as facilitators, especially in natural succession by enriching the nitrogen (N) content in the soil (Gosling, 2005). The method used is vegetation analysis including community similarity index, species richness index, dominance index and important value index. The results obtained from this study are that there are 18 species of understorey identified with two families, namely Cyperaceae (3 species) and Poaceae (15 species). The dominant plant species is Panicum repens. This species was found in L-3 and L-4 with a high number of individuals so that the dominance was also high with values of 0.60 and 0.51 respectively with an INP of 128.13%. The highest IS value of undergrowth is 57.14% at locations 1 and 2 and there is no similarity because the IS value is <75%. The R1 value at the four research sites as a whole can be said to be low because it is less than <3.5. The highest species richness index (R1) was obtained at the second location (L-2) of 1.96, although this value was still low because it was less than <3.5.Suksesi alami penting dalam perkembangan vegetasi, terutama pada lahan yang mengalami kerusakan seperti bekas tambang batu bara. Penambangan batu bara sebagai bahan baku pembuatan bahan bakar, lahan bekas tambangnya mempunyai karakteristik tapak tanpa top soil, tingkat kepadatan tinggi, miskin hara, pH tinggi dan populasi mikorba tanah rendah.Tanaman legum memainkan peran signifikan sebagai fasilitor, terutama memperkaya kandungan nitrogen (N) tanah (Gosling, 2005). Metode yang digunakan yaitu analisis vegetasi meliputi indeks kemiripan komunitas, indeks kekayaan jenis, indeks dominansi dan indeks nilai penting. Hasil yang diperoleh dari penelitian ini yaitu jenis tumbuhan bawah yang teridentifikasi ada 18 jenis dengan dua famili yaitu Cyperaceae (3 jenis) dan Poaceae (15 jenis). Jenis tumbuhan yang mendominasi yaitu jenis Panicum repens. Jenis ini ditemukan pada L-3 dan L-4 dengan jumlah individu yang tinggi sehingga dominansinya juga tinggi dengan masing-masing nilai 0,60 dan 0,51 dengan INP 128,13%. Nilai IS tumbuhan bawah  tertinggi yaitu 57,14% pada lokasi 1 dan 2 dan  tidak ada kemiripan karena nilai IS  <75%. Nilai R1 pada keempat lokasi penelitian secara keseluruhan dapat dikatakan rendah karena kurang dari < 3,5. Indeks kekayaan jenis (R1) tertinggi diperoleh pada lokasi kedua (L-2) sebesar 1,96 meskipun demikian nilai tersebut masih rendah karena dari kurang dari < 3,5.